2000
DOI: 10.1007/pl00008145
|View full text |Cite
|
Sign up to set email alerts
|

Control of carbon partitioning and photosynthesis by the triose phosphate/phosphate translocator in transgenic tobacco plants (Nicotiana tabacum L.). I. Comparative physiological analysis of tobacco plants with antisense repression and overexpression of the triose phosphate/phosphate translocator

Abstract: The physiological properties of transgenic tobacco plants (Nicotiana tabacum L.) with decreased or increased transport capacities of the chloroplast triose phosphate/phosphate translocator (TPT) were compared in order to investigate the extent to which the TPT controls metabolic fluxes in wild-type tobacco. For this purpose, tobacco lines with an antisense repression of the endogenous TPT (alphaTPT) and tobacco lines overexpressing the TPT gene isolated from the C4 plant Flaveria trinervia (FtTPT) were used. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 32 publications
7
33
1
3
Order By: Relevance
“…The potato antisense TPT plants showed only a slight reduction in height, and tuber yield was unchanged compared to WT (Riesmeier et al 1993). However, CO 2 assimilation rates in transgenic tobacco plants with antisense repression of TPT were reduced by about 40% under nonphotorespiratory conditions in comparison to the WT (Ha¨usler et al 2000a(Ha¨usler et al , 2000b. This shows that maximal photosynthetic rates require a fully operational TPT.…”
Section: Introductionmentioning
confidence: 71%
“…The potato antisense TPT plants showed only a slight reduction in height, and tuber yield was unchanged compared to WT (Riesmeier et al 1993). However, CO 2 assimilation rates in transgenic tobacco plants with antisense repression of TPT were reduced by about 40% under nonphotorespiratory conditions in comparison to the WT (Ha¨usler et al 2000a(Ha¨usler et al , 2000b. This shows that maximal photosynthetic rates require a fully operational TPT.…”
Section: Introductionmentioning
confidence: 71%
“…Starch breakdown in the light under photorespiratory conditions provides evidence that circadian or light/dark control of the rate of starch degradation can be overridden by internal signals within the chloroplast in response to carbon deficit. Starch breakdown in the light was also found in plants lacking the triose phosphate transporter grown in high light (Häusler et al, 2000;Walters et al, 2004). Presumably, starch breakdown in the light helps plants overcome a Figure 4.…”
Section: Regulation By Carbon Balancementioning
confidence: 99%
“…2004;Schleucher et al 1998;Weise et al 2004) to provide carbon for subsequent sucrose synthesis and export. Studies on transgenic plants or mutants with decreased TPT activity (Ha¨usler et al 1998(Ha¨usler et al , 2000Heineke et al 1994;Riesmeier et al 1993;Schneider et al 2002), cytoFBPase activity (Sharkey et al 1992;Strand et al 2000;Zrenner et al 1996), phosphoglucose isomerase (Neuhaus et al 1989), or SPS activity (Krause 1994) have shown that when sucrose synthesis is decreased, starch synthesis is up-regulated via the increased PGA/Pi ratio resulting from accumulation of hexose phosphates in the cytosol. As a result, photosynthetic carbon partitioning to starch is increased without altering photosynthesis at ambient CO 2 .…”
Section: Introductionmentioning
confidence: 98%